Effect of surface roughness on pool boiling heat transfer of water on hydrophobic surfaces. (March 2018) - Kim, Jin S.; Girard, Adam; Jun, Seongchul; Lee, Jungho; You, Seung M.
Highlights: Study of surface roughness effect on pool boiling of water on hydrophobic surfaces. Boiling heat transfer coefficients varied with surface roughness and contact angle. Trends related to number of nucleation sites and vapor blanketing. Proposed empirical heat flux correlation with contact angle. Abstract: The effect of surface roughness on the pool boiling of water on hydrophobic surfaces was investigated over the entire boiling regime, from the onset of nucleate boiling to film boiling. The hydrophobic surfaces were fabricated by coating a polytetrafluoroethylene layer on 10 × 10 mm 2 copper surfaces roughened by various sandpapers. The average roughness of the hydrophobic surfaces ranged from 0.042 to 1.54 μm and the corresponding contact angles varied from 116° to 153°. Boiling heat transfer coefficients (BHTC) for the rough surfaces were initially high, but decreased rapidly as the heat flux increased, whereas the BHTCs for the smooth surfaces slowly increased to reach their maximum values and then decreased. The variation in BHTC was explained in terms of the number of nucleation sites and vapor blanketing on the boiling surface, which were related to both the roughness and contact angle. An empirical critical heat flux (CHF) correlation, which showed a 12.2% mean absolute error with the present data, was proposed. Inclusion of the current CHF data for the hydrophobic region provided a complete understanding of the effect of surface roughness and wettability on the CHF in pool boiling of water.